Association between sleep disorders and headache in adolescents: systematic review (Research, Society and Development, 2020)
Objective: The aim of this study is to analyze the association between sleep disorders and headache in adolescents. Materials and Methods: A systematic literature review was carried out, analyzing the publications of articles indexed in the National Library of Medicine (Medline /Pubmed), Scientific Electronic Library Online (Scielo), Cochrane Library and Scopus.The inclusion criteria were as follows: articles in English, with available abstracts; articles that answered the guiding question; and covered the age group of 10 to 19 years old. Advanced search used the descriptors ‘’ Adolescents’’, ‘’ Sleep disorder’’,’’Headache’’, ‘’Quality of life’’, ‘’Poor sleep quality’’ and their synonyms recognized by the Mesch and Desc vocabulary. Results: of the 3.386 articles found, 2.318 articles were selected for having their titles and abstracts read. Among these articles, 41 were selected for reading in full, resulting in the selection of 10 studies to be included in this review. Conclusions: It is concluded that sleep disorders are associated with headache in adolescents, this association being a complex and bidirectional phenomenon that does not allow to clearly distinguish which condition appears first.